A note on double central extensions in exact Mal'tsev categories - Everaert, Tomas (2009)
The characterisation of double central extensions in terms of commutators due to Janelidze (in the case of groups), Gran and Rossi (in the case of Mal'tsev varieties) and Rodelo and Van der Linden (in the case of semi-abelian categories) is shown to be still valid in the context of exact Mal'tsev categories.